Democracy and the church - De Gruchy, John W. (Occasional Papers, 1987)
This paper was part of the proceedings of the first national conference organized by IDASA in Port Elizabeth, South Africa, on 8-9 May, 1987. The author presents some reflections on Christianity and democracy and on the task of the church in a democratic South Africa